Use of Cognitive Task Analysis to Probe Option-Generation in Law Enforcement. (September 2014) - Suss, Joel; Belling, Patrick; Ward, Paul
Option-generation paradigms have been employed successfully to investigate skill-based differences in performance, particularly in complex, dynamic, and/or uncertain domains. However, although knowledge of option-generation behavior (e.g., number of options generated, frequency with which the criterion best option is selected) is informative, the underlying basis for the observed option-generation behavior is not always apparent. To address this issue, we probed option-generation behavior using cognitive task analysis. Experienced and less-experienced law enforcement officers first observed temporally-occluded video simulations, and then completed an option-generation task. The cognitive task analysis comprised elicitation of retrospective verbal reports of thinking, followed by video-stimulated recall; analysis of these data revealed information that potentially explains the observed option-generation behavior and provided information relevant to the design of decision-making training.